1994
DOI: 10.1038/367284a0
|View full text |Cite|
|
Sign up to set email alerts
|

Prediction of bone density from vitamin D receptor alleles

Abstract: Bone density achieved in early adulthood is the major determinant of risk of osteoporotic fracture. Up to 60% of women suffer osteoporotic fractures as a result of low bone density, which is under strong genetic control acting through effects on bone turnover. Here we show that common allelic variants in the gene encoding the vitamin D receptor can be used to predict differences in bone density, accounting for up to 75% of the total genetic effect on bone density in healthy individuals. The genotype associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
898
16
17

Year Published

1996
1996
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,740 publications
(969 citation statements)
references
References 21 publications
38
898
16
17
Order By: Relevance
“…20,21 The associations between ApaI genotype, B lymphopenia and CD8+CD57+ lymphocytosis suggests that the immunoregulatory actions of vitamin D may be modified by the expression and activity of the vitamin D receptor. Existing data suggest that the ApaI A allele is associated with higher VDR expression than the ApaI a allele, 22 and thus would enhance the immunosuppressive actions of calcitriol. This provides a plausible theoretical basis for the association data presented here, but further evidence regarding the physiological effect of the VDR polymorphisms is required.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 The associations between ApaI genotype, B lymphopenia and CD8+CD57+ lymphocytosis suggests that the immunoregulatory actions of vitamin D may be modified by the expression and activity of the vitamin D receptor. Existing data suggest that the ApaI A allele is associated with higher VDR expression than the ApaI a allele, 22 and thus would enhance the immunosuppressive actions of calcitriol. This provides a plausible theoretical basis for the association data presented here, but further evidence regarding the physiological effect of the VDR polymorphisms is required.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, polymorphisms in the 3 0 and 5 0 regions of the gene have been described and variously associated with risk of breast, prostate and colon cancer, although the functional consequences remain to be established clearly (149)(150)(151)(152)(153)(154)(155) . For example, a start codon polymorphism in exon II at the 5 0 end of the gene, determined using the fok-I restriction enzyme, results in a truncated protein (156,157) . At the 3 0 end of the gene three polymorphisms have been identified that do not lead to any change in either the transcribed mRNA or the translated protein.…”
Section: Genetic Resistancementioning
confidence: 99%
“…VDR is essential for 1,25(OH) 2 D 3 to induce the calcemic and phosphatemic effects that normally result in bone mineralization and remodelling [37]. VDR genotypes increase the risk for low BMD and osteoporotic fractures [16,38] and VDR knock-out mice develop a low bone mass phenotype with hypocalcemia, hypophosphatemia, and elevated 1,25(OH) 2 D 3 levels [39]. In addition, reduced serum 25(OH)D levels might predispose young men to stress fractures [40].…”
Section: Discussionmentioning
confidence: 99%
“…Genotyping of the VDR , CTR , and IL-6 variations was performed as described previously [16,18,21,24,25]. Genes that have shown evidence of biological interactions were chosen as candidates for gene-gene interaction analysis [26,27], but only interaction combinations where sample size was large enough were evaluated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation